2013
DOI: 10.1002/jcu.22090
|View full text |Cite
|
Sign up to set email alerts
|

Intrathyroidal parathyroid carcinoma mimicking a thyroid nodule in a MEN type 1 patient

Abstract: A 59-year-old woman with classic manifestations of hyperparathyroidism associated with multiple endocrine neoplasia type 1 presented with a right adrenal mass and two pituitary microadenomas on imaging studies. For evaluation of hypercalcemia, (99m) Tc-MIBI scintigraphy was done and showed focal uptake at the thyroid level of the right anterior neck. Subsequent neck sonography showed several thyroid nodules, but there was no parathyroid tumor. Percutaneous fine-needle aspiration of the dominant thyroid nodule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 13 publications
3
21
0
1
Order By: Relevance
“…In our case, the left upper parathyroid gland was ectopically situated in the thyroid. This anatomical variation made it more difficult to diagnose PC prior to surgery and similar to a case reported by Lee et al [15]. Tamiya et al reported the positive correlation between i-PTH and total calculated volume of parathyroid glands [19].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…In our case, the left upper parathyroid gland was ectopically situated in the thyroid. This anatomical variation made it more difficult to diagnose PC prior to surgery and similar to a case reported by Lee et al [15]. Tamiya et al reported the positive correlation between i-PTH and total calculated volume of parathyroid glands [19].…”
supporting
confidence: 68%
“…Endocrine Journal Advance Publication Discussion PHPT of MEN1 is mostly caused by parathyroid hyperplasia, and PC is quite rare as the causasive lesion with a prevalence reported as 0.28 to 2% [3,5,6]. There were 14 cases of MEN1-associated PC previously reported (Table 2) [5][6][7][8][9][10][11][12][13][14][15][16]. Very high levels of serum Ca and i-PTH, a palpable neck mass, and severe bone disease such as osteitis fibrosa cystica are the specific clinical features of PC [17].…”
mentioning
confidence: 99%
“…In a review of the literature, we found 10 case reports of patients with PC and MEN1 . In our cohort, the prevalence of PC in patients with MEN1 was found to be 0·28% (95% CI, 0–1·4%).…”
Section: Discussionmentioning
confidence: 64%
“…5 In a review of the literature, we found 10 case reports of patients with PC and MEN1. [9][10][11][12][13][14][15][16][17] In our cohort, the prevalence of PC in patients with MEN1 was found to be 0Á28% (95% CI, 0-1Á4%). Our point estimate for prevalence is lower than the reported prevalence of PC in patients with PHP of 0Á74 (95% CI, 0Á53-0Á95), which is based on a systematic review of more than 20 000 patients; however, the confidence intervals overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotally, parathyroid carcinomas are described in MEN1, but this remains rare (del Pozo et al 2011, Lee et al 2014, Singh Ospina et al 2016.…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%